Changes of the fatty acid composition of sprouts during germination - Márton, Melinda-Rita; Szép, Sándor; Mándoki, Zsolt; Tamás, Melinda; Salamon, Rozália Veronika; Salamon, Szidónia; András, Csaba; Csapó, János (Acta Agraria Debreceniensis, 2010)
During our research we studied the fat content and fatty acid composition during the germination and sprouting periods of the most important sprouts: wheat, lentil, alfalfa, radish and sunflower seed. In this article we present our research results during this sprouting study. The concentration of the saturated fatty acids (palmitic acid, stearic acid) decreased, the concentration of the unsaturated fatty acids increased during germination, but the tendency was not so high than was published in the literature.